Deciphering Metamorphism of Tarap Formation through Petrographic Analysis - Muhammad Alfath Salvano Salni; Idarwati Idarwati (Journal of Earth and Marine Technology (JEMT), 2026)
Detailed petrographic characterization aimed at constraining the metamorphic evolution of the Tarap Formation remains limited. This study presents petrographic analyses of 11 metamorphic rock samples collected from the Tarap Formation in OKU Selatan, South Sumatra. The results identify a range of metamorphic rock types, including metalimestone, metasiltstone, calcite–chlorite marble, muscovite–quartz phyllite, quartz–muscovite schist, muscovite–chlorite schist, and quartz–hornblende schist. The protoliths identified were calcareous rocks, quartz–feldspathic sandstones, and shales, which may be lithologically correlated to the Kuantan Formation and Gunungkasih Complex. The metamorphic facies identified are sub-greenschist, greenschist, and lower amphibolite facies. Prograde metamorphism and the subsequent development of mylonitic texture that overprints the main foliation are interpreted to be possibly related to the tectonic evolution of Sumatra during the Early Cretaceous, particularly subduction of the Ngalau Ocean (Meso-Tethys) beneath the Sundaland margin (West Sumatra). The subsequent arc-continent collision from the Late Cretaceous, causing reverse faulting and fold–thrust deformation, facilitated exhumation of the rocks, potentially resulting in retrograde metamorphism and cataclastic texture.